Motivation and job performance among government servants in Johor - Abdul Aziz, Muhammad Zulhusni; Mohamad Yunus, Noor’ain; Adha Hafit, Nor Intan (Universiti Teknologi Mara Selangor, 2024)
Understanding the factors that drive employee performance in the public sector is critical for enhancing organisational efficiency and improving public service delivery. In the context of government servants, motivation plays a pivotal role in influencing job performance, as it determines employee engagement, productivity, and satisfaction. This study examines the relationship between motivation and job performance among government servants in Johor, focusing on identifying the key motivational factors that influence public sector employee performance. A quantitative research design was employed, using a survey method to collect data from 150 government servants. The data were analysed using SPSS Version 28. The findings indicate that rewards, commuting time, and organisational culture significantly influence job performance. However, no significant relationship was found between promotions and job performance, suggesting that traditional assumptions about promotion as a motivator may only partially apply in this context. These results emphasise the importance of understanding how employee motivation shifts across career stages to design more targeted and effective human resource strategies. Organisations can enhance job satisfaction, engagement, and overall productivity by aligning motivational strategies with employees' unique needs at different career stages. This study provides valuable insights for policymakers and human resource practitioners aiming to optimise job performance and employee engagement within the public sector.